2019
DOI: 10.1016/j.najef.2019.03.004
|View full text |Cite
|
Sign up to set email alerts
|

The causality direction of the corporate social responsibility – Corporate financial performance Nexus: Application of Panel Vector Autoregression approach

Abstract: This study is an attempt to model the bidirectional linkages between corporate social responsibility (CSR) and corporate financial performance (CFP) by using the prospective and retrospective approaches. A panel data set for 100 of the Fortune Most Admired Companies was used to study the relationships. Moreover, 1000 firm-year observations were examined between the sample periods of 2007 and 2016. A new methodology known as Panel Vector Autoregression (Panel VAR) approach using the Generalised Method of Moment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
1
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 96 publications
(90 citation statements)
references
References 74 publications
5
68
1
5
Order By: Relevance
“…They found that there is a significant negative short-term impact of CSR adoption and business performance. The CSR-CFP Corporate Financial Performance (CFP) relationship was visited again by several authors (Škare & Golja, 2012;Pätäri, Arminen, Tuppura, & Jantunen, 2014;Vergini, Jacomossi, Turra, & Hein, 2015;Rodriguez-Fernandez, 2016;Carini, Comincioli, Poddi, & Vergalli, 2017;Choongo, 2017;Oh, Hong, & Hwang, 2017;Ang & Weber, 2018;Beck, Frost, & Jones, 2018;Hategan, Sirghi, Curea-Pitorac, & Hategan, 2018;Cherian et al, 2019;Lin, Hung, et al, 2019;Lin, Law, et al, 2019), some of which considered environmental leadership (DiSegni, Huly, & Akron, 2015), its impact on innovation, and firm performance as possible moderating variables (Martinez-Conesa, Soto-Acosta, & Palacios-Manzano, 2017). Ekatah, Samy, Bampton, and Halabi (2011) sought to explore whether CSR is linked to profitability employing simple statistic methods and linear regression.…”
Section: Overview Of the Literaturementioning
confidence: 99%
“…They found that there is a significant negative short-term impact of CSR adoption and business performance. The CSR-CFP Corporate Financial Performance (CFP) relationship was visited again by several authors (Škare & Golja, 2012;Pätäri, Arminen, Tuppura, & Jantunen, 2014;Vergini, Jacomossi, Turra, & Hein, 2015;Rodriguez-Fernandez, 2016;Carini, Comincioli, Poddi, & Vergalli, 2017;Choongo, 2017;Oh, Hong, & Hwang, 2017;Ang & Weber, 2018;Beck, Frost, & Jones, 2018;Hategan, Sirghi, Curea-Pitorac, & Hategan, 2018;Cherian et al, 2019;Lin, Hung, et al, 2019;Lin, Law, et al, 2019), some of which considered environmental leadership (DiSegni, Huly, & Akron, 2015), its impact on innovation, and firm performance as possible moderating variables (Martinez-Conesa, Soto-Acosta, & Palacios-Manzano, 2017). Ekatah, Samy, Bampton, and Halabi (2011) sought to explore whether CSR is linked to profitability employing simple statistic methods and linear regression.…”
Section: Overview Of the Literaturementioning
confidence: 99%
“…In the following, we proceeded to analyze the recent specialized literature that had, like its topic, the study of CSR in correlation with different financial indicators used in this study in order to construct the econometric model. Thus, taking into account the variable fixed asset capitalization, various studies attempted to examine the relationship between CSR and CFP [15,78], with corporate political activity (CPA) serving as the moderator [16], or correlation between CSR and profit [79]. In the study undertaken by Dam and Scholtens [80], the variable liquidity rate was used to investigate "how ownership concentration in European multinational firms is associated with these firms' CSR".…”
Section: Methodsmentioning
confidence: 99%
“…In the study undertaken by Dam and Scholtens [80], the variable liquidity rate was used to investigate "how ownership concentration in European multinational firms is associated with these firms' CSR". The variable rate of sustainable growth has been used in numerous studies to investigate "the effect of CSR on information asymmetry between firms and creditors" [81] and to examine the relationship between CSR and CFP [16], as well as in the relationship between CSR and financial performance [81]. Profitability of using workforce is one of the variables often used in studies to "investigate the relationship between the budget related to CSR, innovation, and training, defined as sustainable factors, and the financial results of small and medium-sized enterprises (SMEs)" [19], to examine the correlation between CSR and financial performance, to examine the relationship between CFP and CSR, as well as the relationship between corporate social responsibility activities (CSRA) and human capital (HC) and the relationship between HC and CFP [82].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations